Analisis Metode Team Games Tournament Terhadap Kemampuan Menulis Naskah Berita pada Pembelajaran Bahasa Indonesia Kelas Xi Mastahfizil Qur’an - Siregar, Rodia Tammardia; Gajah, Ewin Sanjaya; Panjaitan, Devi Hertina; Azzahra, Annisa; Maulani, Syafina; Marpaung, Ayu Anggreini (Indo-MathEdu Intellectuals Journal, 2025)
The Team Games Tournament (TGT) learning model is applied in Indonesian language learning to improve the news text writing skills of grade XI students at MASTAHFIZIL QUR’AN. The purpose of this study was to determine and describe the effectiveness of the TGT model application in improving news text writing skills. The data collection techniques used were observation, interviews, and written tests which were then analyzed descriptively. Based on the research conducted, it was found that the TGT application was able to improve students’ abilities in understanding the structure of news texts, and organizing information systematically. This model also creates an interactive learning atmosphere through competition and group cooperation. In addition, TGT has a positive impact on students’ critical thinking skills, collaboration, communication, and creativity. Researchers also found several obstacles, such as the difficulty of students adapting to the group-based learning system. These obstacles can be overcome through intensive guidance from teachers. Researchers concluded that the TGT model not only improves students’ writing skills, but also strengthens social interaction and a sense of responsibility in group-based learning